Analisis Penerapan Pengendalian Internal Prosedur Penyaluran Kredit Multiguna pada PT Bank Sumut KC.Ngumban Surbakti - Tarigan, Rosani; Saribu, Ardin Dolok; Hutapea, Herti Diana (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
This investigation aims to find out the analysis of the application of the internal control system of multi-purpose credit distribution procedures in Sumut Bank KC.Ngumban Surbakti. The procedures for granting multi-purpose loans are structured from the stage of application, analysis, recommendation, approval, warning, and credit liquidation. The internal credit control system has five conceptual elements: control environment, risk assessment, control activities, information and communication, and monitoring. This type of research is qualitative, describing the application of the internal control system of multi-use credit distribution procedures in the Sumut Bank of KC. The data used is the primary data used to determine the implementation of the internal control system of credit granting through interviews. The final results of this study show that the implementation of the internal control system of multi-use credit distribution procedures in PT.Bank Sumut KC.Ngumban Surbakti has been fully carried out. Internal control system of non-executed multi-use credit distribution, i.e. control and monitoring activities through the 5C credit principle, which is the ability and purpose of the application. With the failure of the system of internal control of giving credit fully then the internal control system of granting multi-purpose credit to the PT.Bank Sumut KC.Ngumban Surbakti is not in line with its purpose.